Pengaruh Flash Sale, Free Shipping Promotion Dan Online Customer Rating Terhadap Keputusan Pembelian Kalangan Generasi Z Pada Produk Beauty And Care Di Aplikasi Tokopedia - Fauzan, Mohammad Fariz; Ratnasari, Ina (Jurnal Ilmiah Wahana Pendidikan, 2024)
In this study focuses on analyzing the influence of flash sales, free shipping promotions and online customer ratings on purchasing decisions on the Tokopedia marketplace. Quantitative methods were used in carrying out this research along with descriptive and verification approaches. The primary data is in the form of a questionnaire, the purposive sampling technique is the technique in collecting data in this study. Gen Z people in Indonesia who have purchased beauty and care products on the Tokopedia application are an unlimited population in this study, then processed using the Cochran formula to determine a sample of 385. The success of this study used SPSS 26 and Microsoft Excel 2019. This research provides the fact that there is a partial significant relationship between Flash Sale worth 23.7%, Free Shipping Promotion worth 55.2% and Online Customer Rating worth 27.3% on Tokopedia Purchase Decision. Furthermore, there is the influence of the simultaneous relationship of Flash Sale, Free Shipping Promotion and Online Customer Rating to Tokopedia Purchase Decisions, with a simultaneous value contribution of 44.8% and other variables that are not part of this study as much as 55.2%.